Placental transfer and vascular effects of pharmaceutical drugs in the human placenta ex vivo: A review. (May 2022) - van Hove, H.; Mathiesen, L.; Freriksen, J.J.M.; Vähäkangas, K.; Colbers, A.; Brownbill, P.; Greupink, R.
Abstract: At least 80% of pregnant woman in Europe use at least one medication during their pregnancy. The majority of these drugs are prescribed off-label. A better understanding of drug transport and effects in the placenta can provide an improved pharmacological basis to rationalize drug and dose selection for prescription. Here we provide a narrative review of studies that used the ex vivo placenta perfusion model to study placental drug transport and vascular effects of pharmaceuticals. For studies on placental transfer, we found that the methodology used varied substantially between studies as well as the way in which data was reported. Across the different therapeutic groups, e x vivo measurements of transfer generally corresponded well to in vivo findings. Still, further standardization of the perfusion technique would facilitate a broader use of perfusion data, e.g. in the context of quantitative systems pharmacology models as has been explored in recent years. Only few studies investigated the effects of drugs on the vascular tone using the ex vivo dual-side perfusion model. The model was particularly applied to study vasodilatory effects of pharmaceuticals in the fetoplacental circulation. In conclusion, the ex vivo dually perfused human cotyledon provides a relevant system to gain insights in placental drug disposition and study effects on the fetoplacental vasculature. Highlights: Perfusions provide insight in transport of pharmaceuticals across the placental barrier. Perfusion studies can be used to study the vascular effects of pharmaceutical drugs. The impact of placenta perfusions can be further improved by standardization.